2007
DOI: 10.1093/rheumatology/ken058
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of dermal fibrosis induced by one-time injection of bleomycin-poly(L-lactic acid) microspheres

Abstract: The present study demonstrated for the first time that one-time injection of BLM-PLA microspheres can induce dermal fibrosis in C3H mice. BLM-PLA microspheres thus offer a labour-saving, simple and powerful tool to establish an animal model of BLM-induced dermal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In chronically inflamed tissue, periostin was largely absent from the ECM particularly in areas associated with high inflammatory infiltration. Inset shows primary delete control an important determinant of skin homeostasis, and alterations of the ECM constituents can result in abnormal tissue function (Li et al 2007;Shibusawa et al 2008). We have recently confirmed that periostin is expressed in human and murine skin (Jackson-Boeters et al 2009), and periostin knockout mice display a reduction in dermal thickness .…”
Section: Discussionmentioning
confidence: 82%
“…In chronically inflamed tissue, periostin was largely absent from the ECM particularly in areas associated with high inflammatory infiltration. Inset shows primary delete control an important determinant of skin homeostasis, and alterations of the ECM constituents can result in abnormal tissue function (Li et al 2007;Shibusawa et al 2008). We have recently confirmed that periostin is expressed in human and murine skin (Jackson-Boeters et al 2009), and periostin knockout mice display a reduction in dermal thickness .…”
Section: Discussionmentioning
confidence: 82%
“…The wounds were excised and analyzed at 3 different time points on days 2, 7, and 14, which represent the inflammatory, proliferative, and remodeling stages of wound healing, respectively. Another group of mice received either repeated injections of 100 mg BLM daily for 28 days (Yamamoto et al, 1999), or a single subcutaneous injection of 0.4 ml of PLA microsphere suspension containing 13 mg BLM that had been described to induce the same degree of dermal fibrosis as the repeated daily BLM injections for 28 days (Shibusawa et al, 2008). Dermal tissues were obtained from 3 to 4 mice in each group on the indicated days after treatment, and subjected to hematoxylin and eosin or Sirius red-Fast green FCF staining (LopezDe Leon and Rojkind, 1985) and luciferase assays to analyze the histopathological findings and the activation of Col1a2 promoter, respectively.…”
Section: Bm Transplantationmentioning
confidence: 99%
“…Due to the lack or shortage of this enzyme in the lungs and the skin, bleomycin‐induced fibrosis and sclerosis occurs predominantly in these organs. A recent report shows that a one‐time injection of bleomycin‐poly ( l ‐lactic acid) microspheres can induce dermal sclerosis in mice 18 . The induction of dermal sclerosis is considered to be, in part, mediated by inflammatory and fibrogenic cytokines, as well as by the direct effect of bleomycin on ECM synthesis in fibroblasts.…”
Section: Bleomycin‐induced Scleroderma Modelmentioning
confidence: 99%